Determinants of Working Capital Investment: A Study of Malaysian PublicListed Firms - Shaista Wasiuzzaman; Veeri Chettiar Arumugam (Australasian Accounting, Business and Finance Journal, 2013)
The paper examines the determinants of the level of investment in net operating working capital by firms in Malaysia. Data from 192 companies spanning a period of 8 years (2000- 2007) are analysed using the OLS regression technique for this purpose. The study finds that in times of economic expansion, younger and smaller firms with less tangible assets, low leverage, high immediate sales growth, high operating cash flows, less volatile revenues and low levels of asymmetric information are likely to have the highest investments in operating working capital. Board characteristics, namely size and the independence of the board, are not found to have any significant influence on the working capital investment of firms.
Keywords: Working capital investment; pecking order theory; asymmetric information; board characteristics